2014
DOI: 10.1039/c4ra02987a
|View full text |Cite
|
Sign up to set email alerts
|

In vitro osteogenesis of mesenchymal stem cells promoted by the release of La3+ and SiO44− from sheet-shaped lanthanum dropped hexagonal mesoporous silicon

Abstract: In this study, in vitro osteogenesis was successfully promoted in mouse mesenchymal stem cells (BMSCs) by the release of La 3+ and SiO 4 4À from a sheet-shaped lanthanum dropped hexagonal mesoporous silica (La-HMS). In comparison with previous nano-sphere shaped La-HMS, the sheet-shaped morphology was similar to the inorganic component of bone, which could provide better toughness during bone repair and regeneration. The successful incorporation of La 3+ into the HMS was confirmed by the results of XRD and ICP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…At the same time, the difference between the diameters of La and Si atoms will lead to more defects in the mesoporous skeleton. This further accelerated the degradation rate of LMS and La 3+ release, in agreement with other studies 16 , 19 . Compared with LMS-1–3, the addition of more La sources in the preparation process of LMS-4 leads to more lattice defects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the same time, the difference between the diameters of La and Si atoms will lead to more defects in the mesoporous skeleton. This further accelerated the degradation rate of LMS and La 3+ release, in agreement with other studies 16 , 19 . Compared with LMS-1–3, the addition of more La sources in the preparation process of LMS-4 leads to more lattice defects.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that La-doped inorganic ceramics could stimulate and enhance osteogenic differentiation. Especially the La-doped bioceramics or their composites with polymer biomaterials 16 , 17 . However, due to the degradation performance of bioceramics, it is difficult to control the release of trace La 3+ in doped bioceramics 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to substitution of Ca 2+ ions with La 3+ within bone and, through this continuous remodelling cycle of bone, lanthanides can affect cellular activity and potentially exert a positive influence on bone mineral. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…This can lead to substitution of Ca 2+ ions with La 3+ within bone and, through this continuous remodelling cycle of bone, lanthanides can affect cellular activity and potentially exert a positive inuence on bone mineral. 20,21 Lanthanum, in the form of lanthanum carbonate (La 2 (CO 3 ) 3 , Fosrenol™) is currently used to treat hyperphosphatemia, a condition caused by elevated phosphate levels in the blood. There is a demonstrated dose-dependent accumulation of lanthanum in bone with long retention times.…”
Section: Introductionmentioning
confidence: 99%